2023
DOI: 10.1021/acs.chemrestox.3c00100
|View full text |Cite
|
Sign up to set email alerts
|

Is Baikiain in Tara Flour a Causative Agent for the Adverse Events Associated with the Recalled Frozen French Lentil & Leek Crumbles Food Product? - A Working Hypothesis

Abstract: The French Lentil & Leek Crumbles frozen food product was recently recalled due to reports of gastrointestinal issues. So far, 393 adverse illness complaints and 133 hospitalizations have been reported from consumption of this food, and the tara (Tara spinosa) protein flour ingredient is hypothesized to be responsible. A multipronged approach resulted in identification of (S)-(−)-baikiain in tara as a compound of interest due to its abundance, possible metabolic fate, and close resemblance to irreversible inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…Of the 27 different components in FLLC, Tara flour was the suspected cause of the injury as this ingredient had never been used in prior Daily Harvest™ products. 7 Tara flour is a plant-based protein extracted from the seeds of the South American tree Tara spinosa (Feuillé ex Molina) Britton & Rose (synonym: Caesalpinia spinosa (Molina) Kuntze). Tara spinosa is primarily cultivated in Peru which is responsible for more than 80% of the world supply.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 27 different components in FLLC, Tara flour was the suspected cause of the injury as this ingredient had never been used in prior Daily Harvest™ products. 7 Tara flour is a plant-based protein extracted from the seeds of the South American tree Tara spinosa (Feuillé ex Molina) Britton & Rose (synonym: Caesalpinia spinosa (Molina) Kuntze). Tara spinosa is primarily cultivated in Peru which is responsible for more than 80% of the world supply.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical analysis of FLLC confirmed the presence of Tara flour and absence of toxic compounds, microbial pathogens, mycotoxins, major allergens, pesticides, hepatitis A, norovirus and therefore, the Tara flour itself was implicated as the likely source of hepatotoxin. 7 The component in Tara flour responsible for the injury was assessed in studies by Chittiboyina et al who demonstrated high concentrations of baikiain, an uncommon, non-protein amino acid. Baikiain was considered the likely cause as under physiological conditions, it could be metabolised into a reactive intermediate-4,5epoxypipecolic acid presumably via cytochrome P450 oxidation or 4or 5-hydroxypipecolic acid via hydration that could lead to glutathione depletion by inactivation of detoxification enzymes, such as flavoenzyme l-pipecolate oxidase (PIPOX), whose reduction in tissue culture models can potentiate hydrogen peroxide mediated injury.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations